City-wide monitoring and contributing factors to shallow subsurface temperature variability in Nanjing, China. (November 2022) - Zhang, Tiansheng; Liu, Chun; Bayer, Peter; Zhang, Liwei; Gong, Xulong; Gu, Kai; Shi, Bin
Abstract: Shallow temperatures down to a depth of 100 m were measured over one year in 19 closed boreholes located in Nanjing, China, to reveal the conditions and factors influencing the subsurface thermal regime. A monitoring concept with distributed temperature sensing, fiber Bragg grating-based sensor, and a type of Resistance Temperature Detectors, is implemented, providing spatial distribution characteristics of subsurface temperatures. The results show that temperatures near the surface are most dynamic, influenced by the air temperature. The temperature remains stable at the depth of 10–20 m. The mean transition temperature is 18.1 °C. Borehole measurements are interpolated by using satellite images and surface temperature records to obtain large-scale surface temperature distributions and temporal variations of subsurface temperature. Geological and hydrological conditions are primary factors by affecting subsurface upward heat flux and heat loss. Urban land cover change and enhanced heat release from urbanization contribute to a subsurface urban heat island with intensities of 1.0–4.4 °C. The altered subsurface thermal regime is of primary concern for the management of shallow geothermal energy use. The monitoring concept in this study can provide spatially-temporally continuous profiles of subsurface temperature and become a reference for city-wide geothermal monitoring in other urban areas.